2017
DOI: 10.1007/s00234-017-1907-y
|View full text |Cite
|
Sign up to set email alerts
|

Added value of multiphase CTA imaging for thrombus perviousness assessment

Abstract: PurposeThrombus perviousness has been associated with favorable functional outcome in acute ischemic stroke (AIS) patients. Measuring thrombus perviousness on CTA may be suboptimal due to potential delay in contrast agent arrival in occluded arteries at the moment of imaging. Dynamic sequences acquired over time can potentially overcome this issue. We investigate if dynamic CTA has added value in assessing thrombus perviousness.MethodsProspectively collected image data of AIS patients with proven occlusion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
20
2
Order By: Relevance
“…An analysis in multiphase CTA imaging was previously performed to resolve the time issue but showed an optimal association between perviousness and functional outcome on arterial-phase CTA, rather than delayed phases, which we have not used in our cohort. 23 Despite a certain statistical spread in our results, an association of thrombus perviousness with the main constituents FP and RBC was shown in the histological study cohort. The fibrin-rich thrombus, assumed to have a higher degree of organization, 13 seems to allow the contrast agent to penetrate the clot more easily, which fits with the results of previous studies on artificial thrombi.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…An analysis in multiphase CTA imaging was previously performed to resolve the time issue but showed an optimal association between perviousness and functional outcome on arterial-phase CTA, rather than delayed phases, which we have not used in our cohort. 23 Despite a certain statistical spread in our results, an association of thrombus perviousness with the main constituents FP and RBC was shown in the histological study cohort. The fibrin-rich thrombus, assumed to have a higher degree of organization, 13 seems to allow the contrast agent to penetrate the clot more easily, which fits with the results of previous studies on artificial thrombi.…”
Section: Discussioncontrasting
confidence: 66%
“…1 The use of arterial-phase CTA appeared to be most suitable for the measurement of thrombus perviousness when compared with delayed phases. 23 The assessment of perviousness measures is easy to implement during admission imaging of patients with stroke that consists of noncontrast CT (nCT) and CTA imaging and has the potential to give additional information about the occluding thrombus.…”
mentioning
confidence: 99%
“…Regarding perviousness measurements, different opinions about optimal techniques exist. While one study [19] favored the dynamic CTA for perviousness assessment due to better outcome prediction after reperfusion therapy than conventional single-phase CTA, another study [26] showed that the use of an arterial-phase CTA appeared to be most suitable for the measurement of thrombus perviousness compared to delayed phases. Arterial-phase CTA is broadly available and commonly used in stroke centers, an essential requirement for a parameter that is intended to be used within the clinical workflow.…”
Section: Discussionmentioning
confidence: 99%
“…If effortful acquisition or image postprocessing is necessary, a broad acceptance in clinical practice seems unlikely. Therefore, CTA-index has one key advantage over perviousness measures: it does not require a co-registration process [14,18,26]. It is based on a standard imaging technique of the clinical routine.…”
Section: Discussionmentioning
confidence: 99%
“…14,21 A previous study using 3-phase CTA found that arterial phase CTA was superior to venous phase CTA (8 seconds after arterial phase CTA) or delayed-phase CTA (16 seconds after arterial phase CTA) to assess the TAI. 22 However, 3-phase CTA did not cover enough time points, and the optimal phase could be located between the arterial phase and venous phase. Thus, we believe dynamic CTA derived from CTP was better for evaluating clot perviousness.…”
Section: Discussionmentioning
confidence: 99%